Posterior Oropharyngeal Saliva for the Detection of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). (21st June 2020) - Wong, Sally Cheuk Ying; Tse, Herman; Siu, Hon Kei; Kwong, Tsz Shan; Chu, Man Yee; Yau, Felix Yat Sun; Cheung, Ingrid Yu Ying; Tse, Cindy Wing Sze; Poon, Kin Chiu; Cheung, Kwok Chi; Wu, Tak Chiu; Chan, Johnny Wai Man; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has put tremendous pressure on the healthcare system worldwide. Diagnostic testing remained one of the limiting factors for early identification and isolation of infected patients. This study aimed to evaluate posterior oropharyngeal saliva (POPS) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection among patients with confirmed or suspected COVID-19. Methods: The laboratory information system was searched retrospectively for all respiratory specimens and POPS requested for SARS-CoV-2 RNA detection between 1 February 2020 and 15 April 2020. The agreement and diagnostic performance of POPS against NPsp were evaluated. Results: A total of 13772 specimens were identified during the study period, including 2130 POPS and 8438 nasopharyngeal specimens (NPsp). Two hundred and twenty-nine same-day POPS-NPsp paired were identified with POPS and NPsp positivity of 61.5% (95% confidence interval [CI] 55.1–67.6%) and 53.3% (95% CI 46.8–59.6%). The overall, negative and positive percent agreement were 76.0% (95% CI 70.2–80.9%), 65.4% (95% CI 55.5–74.2%), 85.2% (95% CI 77.4–90.8%). Better positive percent agreement was observed in POPS-NPsp obtained within 7 days (96.6%, 95% CI 87.3–99.4%) compared with after 7 days of symptom onset (75.0%, 95% CI 61.4–85.2%). Among the 104 positive pairs, the mean difference in Cp value was 0.26 (range: 12.63 to −14.74), with an overall higher Cp value in NPsp (Pearson coefficient 0.579). No significant temporal variation was noted between the 2 specimen types. Conclusions: POPS is an acceptable alternative specimen to nasopharyngeal specimen for the detection of SARS-CoV-2.